2012
DOI: 10.1002/ijc.27485
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus types in 115,789 HPV‐positive women: A meta‐analysis from cervical infection to cancer

Abstract: Genotyping may improve risk stratification of high-risk (HR) human papillomavirus (HPV)-positive women in cervical screening programs; however, prospective data comparing the natural history and carcinogenic potential of individual HR types remain limited. A meta-analysis of cross-sectional HR HPV-type distribution in 115,789 HPV-positive women was performed, including 33,154 normal cytology, 6,810 atypical squamous cells of undetermined significance (ASCUS), 13,480 low-grade squamous intraepithelial lesions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

101
746
17
24

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 794 publications
(888 citation statements)
references
References 31 publications
101
746
17
24
Order By: Relevance
“…HPV33 ranked first based on PPV thus showing strong association with present and future CIN2+ and CIN3+ risk. This result is consistent with other recent reports which found a strong association between HPV33 and high‐grade CIN despite a much weaker association with invasive cancer 8, 24, 25, 26, 27. Conversely, the importance of HPV35 based on PPV was more unexpected even though a previous analysis within the future study28 reported a high probability of transition from HPV35 incident infection to CIN2 and CIN3 lesions after 3 years of follow‐up.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…HPV33 ranked first based on PPV thus showing strong association with present and future CIN2+ and CIN3+ risk. This result is consistent with other recent reports which found a strong association between HPV33 and high‐grade CIN despite a much weaker association with invasive cancer 8, 24, 25, 26, 27. Conversely, the importance of HPV35 based on PPV was more unexpected even though a previous analysis within the future study28 reported a high probability of transition from HPV35 incident infection to CIN2 and CIN3 lesions after 3 years of follow‐up.…”
Section: Discussionsupporting
confidence: 92%
“…Genotyping was blind to cytology and histology and its completeness within the areas/phases in which it was done was high and plausibly unselected. On the other hand, despite the large size, the precision of estimates for some less frequent HPV types is low and random variation could explain the differences between our observations and those obtained in other studies 8, 44. Previous screening intensity can account for differences in PPV compared to other studies24 and local variations in type distribution can result in differences in sensitivity and specificity.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…The focus is on HPV16, the most frequent and most carcinogenic type,12, 13 which is also the most difficult to control by vaccination8 due to its special propensity to persist. In a previous study,14 using idealized sexual contact structures, we have shown how HPV control through vaccination becomes more challenging in a population transitioning from a traditional to a gender‐equal sexual behavior.…”
Section: Introductionmentioning
confidence: 99%